2017
DOI: 10.1139/as-2016-0021
|View full text |Cite
|
Sign up to set email alerts
|

Biotic responses to multiple aquatic and terrestrial gradients in shallow subarctic lakes (Old Crow Flats, Yukon, Canada)

Abstract: Biotic communities in shallow northern lakes are frequently used to assess environmental change; however, complex interactions among multiple factors remain understudied. Here, we present analyses of a comprehensive data set that evaluates the influence input waters, catchment characteristics, limnology, and sediment properties on diatom and chironomid assemblages in surface sediments of~49 shallow mainly thermokarst lakes in Old Crow Flats, Yukon. Multivariate analyses and ANOSIM tests identified that composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 116 publications
1
19
0
Order By: Relevance
“…Shallow lakes in the arctic and subarctic provide an opportunity to assess the influence of ecological drift (as opposed to environmental filtering) on periphytic diatom communities. In the Old Crow Flats, previous aquatic community studies determined that spatially variable selection exerts only weak control on diatom communities (Balasubramaniam et al 2017). Our analyses support this conclusion, as we found weak and non-significant concordance between diatom community composition and a comprehensive matrix of hydrologic and water quality parameters, regardless of lake size.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Shallow lakes in the arctic and subarctic provide an opportunity to assess the influence of ecological drift (as opposed to environmental filtering) on periphytic diatom communities. In the Old Crow Flats, previous aquatic community studies determined that spatially variable selection exerts only weak control on diatom communities (Balasubramaniam et al 2017). Our analyses support this conclusion, as we found weak and non-significant concordance between diatom community composition and a comprehensive matrix of hydrologic and water quality parameters, regardless of lake size.…”
Section: Discussionsupporting
confidence: 84%
“…Periphytic diatoms provide an opportunity to test the influence of drift on a biotic community because of their rapid growth cycles, small size and high abundance relative to larger organisms, and well-established taxonomy. Previous work in the Old Crow Flats (Yukon, Canada), a northern lake-rich landscape, found that water chemistry best explained the diatom community assembly deposited in lake sediment when compared to sediment and catchment properties, but only accounted for 17.18% of the variance in community composition (Balasubramaniam et al 2017). Unexplained variance in the diatom community could potentially be attributed to stochastic processes, namely ecological drift.…”
Section: Introductionmentioning
confidence: 93%
“…2015; Balasubramaniam et al . 2017). This is observed at Lake PG03, where shifts in assemblages are likely the result of changes in aquatic habitat.…”
Section: Discussionmentioning
confidence: 99%
“…Although aquatic production in Arctic lakes is known to be principally governed by temperature, the influence of habitat has also been shown to be important (Lotter & Bigler 2000;Medeiros et al 2015;Balasubramaniam et al 2017). This is observed at Lake PG03, where shifts in assemblages are likely the result of changes in aquatic habitat.…”
Section: Influences Of Habitat On Chironomid Productivitymentioning
confidence: 99%
See 1 more Smart Citation